2020
DOI: 10.5296/jas.v8i4.17598
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Nile Tilapia and vegetables Grown in Different Aquaponic Volumes

Abstract: The objective of this study was to evaluate the performance of Nile tilapia and the lettuce, watercress, and arugula vegetables in a gravel-bed aquaponic system using the aerated fish tank-to-vegetable growing bed volume ratios of 1:1 and 1:2. Each experimental unit consisted of an aquaponic module composed of two containers: one to allocate the vegetables (500-L tank with gravel, measuring 2 m2) and another to stock fish at the ratios of 1:1 (500-L vegetable:500-L fish tank) and 1:2 (500-L vegetable tank:1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Indeed, the educational use of aquaponics system [69] and life cycle assessment modeling [70] necessitated the use of rocket plants in mixture with many other crops; thus, the results could not be compared with ours. Barbosa et al [71] examined rocket growth under two different system water volumes, and their results indicated poor growth performance reaching 8-15 times lower leaves fresh weight compared to ours, mainly due to extremely high sowing density of seedlings. Finally, Lennard and Ward [72] concluded that rocket does not adapt to aquaponic culture as well as other herbs, because they found increased plant growth in the hydroponics system.…”
Section: Plant Growth Performancementioning
confidence: 52%
“…Indeed, the educational use of aquaponics system [69] and life cycle assessment modeling [70] necessitated the use of rocket plants in mixture with many other crops; thus, the results could not be compared with ours. Barbosa et al [71] examined rocket growth under two different system water volumes, and their results indicated poor growth performance reaching 8-15 times lower leaves fresh weight compared to ours, mainly due to extremely high sowing density of seedlings. Finally, Lennard and Ward [72] concluded that rocket does not adapt to aquaponic culture as well as other herbs, because they found increased plant growth in the hydroponics system.…”
Section: Plant Growth Performancementioning
confidence: 52%